(untitled) (Rivista italiana di Paleontologia e Stratigrafia, 2018)
In this paper we document in detail the transition from the Rosso Ammonitico Lombardo to the Radiolarites outcropping at Alpe Turati (Albavilla, Como) in the Lombardy Basin of the Southern Alps. At this location, the Jurassic succession was deposited on a flank of the Corni di Canzo paleohigh: as found on other structural shallow areas, the upper Pliensbachian–Toarcian–Aalenian interval is represented by pseudonodular to nodular marly limestones of the Morbio Limestone and Rosso Ammonitico Lombardo units. In the early Bajocian deposition of biosiliceous sediments is ubiquitously testified by the Radiolarites (Bajocian–Callovian). At Alpe Turati, the interval immediately below the basal green member of the latter unit, consists of a 10 cm thick black shale, pointing to oxygen-depleted bottom waters. Dysoxia persisted during the Bajocian–Callovian as evidenced by dark green stratified cherts. Calcareous nannofossil biostratigraphy indicate an early Bajocian age for the black shale that correlates with the core of a distinct C isotopic negative anomaly also known in various basins outside the Southern Alps. Very dark grey to black lithologies of early Bajocian age have been documented in a few sections from Poland, Corsica and Morocco. We name Gaetani Level the black shale interval in recognition of Maurizio Gaetani’s pioneering and extensive work on Jurassic sedimentary successions of the Lombardy Basin. The association of the Gaetani black shale with a C isotopic anomaly suggests that it could be the sedimentary record of an Oceanic Anoxic Event whose regional to global extension must be ascertained.